2009
DOI: 10.1016/j.jhazmat.2008.05.104
|View full text |Cite
|
Sign up to set email alerts
|

Zn(II) adsorption from synthetic solution and kaolin wastewater onto vermicompost

Abstract: The adsorption of Zn(II) from both synthetic solution and kaolin industry wastewater by cattle manure vermicompost was studied. The adsorption process was dependent on the various operating variables, viz., solution pH, particle size of the vermicompost, mass of vermicompost/volume of the Zn(II) solution ratio, contact time and temperature. The optimum conditions for Zn adsorption were pH 6.0, particle size of < or = 250 microm, 1 g per 10 mL adsorbent dose, contact time of 4h and temperature of 25 degrees C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A review of the literature has shown that there are only a few studies reporting the remediation of wastewaters containing heavy metals by vermicomposts. The efficiency of vermicompost for removing heavy metals from aqueous solutions or industrial effluents has not been studied in detail except to mention a few and namely Jordão et al (2002Jordão et al ( , 2009, Arruda (2003), Carrasquero Durán et al (2006), Jadia and Fulekar (2008) and Urdaneta et al (2008). These researchers found that metal concentrations in the purified effluents were below the maximum values established for waste discharges by the prevalent local standards.…”
Section: Characteristics Of Vermicompostmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature has shown that there are only a few studies reporting the remediation of wastewaters containing heavy metals by vermicomposts. The efficiency of vermicompost for removing heavy metals from aqueous solutions or industrial effluents has not been studied in detail except to mention a few and namely Jordão et al (2002Jordão et al ( , 2009, Arruda (2003), Carrasquero Durán et al (2006), Jadia and Fulekar (2008) and Urdaneta et al (2008). These researchers found that metal concentrations in the purified effluents were below the maximum values established for waste discharges by the prevalent local standards.…”
Section: Characteristics Of Vermicompostmentioning
confidence: 99%
“…Their results showed maximum adsorption values between 113.6 mg/g (33°C) and 123.5 mg/g (50°C), and the differences in the IR spectra at pH 3.8 and 7.0 in the region from 1,800 to 1,300/cm, were interpreted on the basis of the carboxyl acid ionization, which reduced the band intensity around 1,725/cm, producing signals at 1,550/cm and 1,390/cm of carboxylate groups. Jordão et al (2009) also studied the adsorption of Zn 2? from both synthetic solution and kaolin industry wastewater by cattle manure vermicompost.…”
Section: Vermicompost-heavy Metal Biosorptionmentioning
confidence: 99%
“…Although the Al concentration in the wastewater reached up to 102 mg L −1 , the concentration of this metal seems to vary according to the time of sample collection. In a previous work, Jordão et al (2008) reported Al concentration in the kaolin wastewater from Mar de Espanha of 585 mg L −1 , while Fe concentration reached up to 710 mg L −1 . There is no maximum limit of Al concentration established by the Brazilian legislation for effluent discharges into water courses.…”
Section: Resultsmentioning
confidence: 94%
“…However, some metals are not strongly influenced on varying the particle size, while some are better adsorbed only onto smaller particles (Matos and Arruda 2003). Jordão et al (2008) reported that Zn(II) adsorption by cattle manure vermicompost was higher in the ≤250 fraction as compared with any other fraction studied. In the present study, the ≤250 fraction particle size was used in the Al(III) and Fe(II) adsorption experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For example, compost incorporation enhances the stabilization of mine-associated soils, thus reducing symptoms of ecotoxicity (Gadepalle et al 2007;Tandy et al 2009b), although these remediative effects may be moderated or reversed in certain composts . Organic constituents of vermicomposts also have high-metal affinities (Pereira and Arruda 2003;Carrasquero Durán et al 2006), and there is an emerging interest in the use of vermicomposts for removing metals from industrial effluents (Jordão et al 2002(Jordão et al , 2007Jordão, Fernandes, Ribeiro, Nascimento, et al 2009). In these seminal studies vermicomposts were deployed as a cation-exchange matrix.…”
Section: Composts In the Remediation Of Metalliferous Soilsmentioning
confidence: 99%